2003
DOI: 10.1007/s00268-002-6659-z
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Results of Partial Pancreaticoduodenectomy for Ductal Adenocarcinoma of the Pancreatic Head: 25‐Year Experience

Abstract: The prognosis of patients who undergo resection for pancreatic ductal adenocarcinoma with curative intention is generally poor unless they have early-stage disease. Based on our 25-year experience, the results of 194 patients after a standardized Kausch-Whipple resection for adenocarcinoma of the pancreatic head were analyzed and the prognostic factors were evaluated. Between 1972 and 1998 a total of 221 patients were diagnosed for ductal adenocarcinoma of the pancreatic head, and 194 of them subsequently unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
210
2
26

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(260 citation statements)
references
References 41 publications
14
210
2
26
Order By: Relevance
“…Clinically, PDAC is often diagnosed at a late stage, when local invasion of vital structures and distant metastasis has already precluded curative resection. Consequently, only B10-20% of the patients are candidates for surgery at the time of diagnosis, of which only approximately 25% will survive for more than 5 years (Yeo et al, 1997;Richter et al, 2003;Wagner et al, 2004). Moreover, PDAC is often highly resistant to the currently available chemotherapeutics as well as radiotherapy (Klinkenbijl et al, 1999;Neoptolemos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PDAC is often diagnosed at a late stage, when local invasion of vital structures and distant metastasis has already precluded curative resection. Consequently, only B10-20% of the patients are candidates for surgery at the time of diagnosis, of which only approximately 25% will survive for more than 5 years (Yeo et al, 1997;Richter et al, 2003;Wagner et al, 2004). Moreover, PDAC is often highly resistant to the currently available chemotherapeutics as well as radiotherapy (Klinkenbijl et al, 1999;Neoptolemos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 Current scenario in such a tricky situation is a difficult proposition as outcome with other alternative therapies are not acceptable in terms of survival and quality of life. [6][7][8] Some recent reports show improved survival with Gemcitabine as a first line of therapy. 9 In the present series males are the sufferers of pancreatic cancer, out of 62 patients, 48 (77.41%) males, 14 patients (22.59%) females, age group was 33 to 65 years with mean age between 45 to 55 years.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 When surgical resection was compared with radio chemotherapy for resectable pancreatic cancer, patients in operative group done fairly well with median survival of 17 months versus 11 months in chemoradiation group. 6,7 Few studies report improvements especially with regard to quality of life, are primarily due to use of gemcitabine as first line chemotherapy. 8 Standardized surgical treatment for head of pancreas cancer, duodenal cancer, distal cholangiocarcinoma, periampullary cancer was Whipple's or it's pylorus preserving modification.…”
Section: Introductionmentioning
confidence: 99%
“…Complete surgical resection with R0 negative margins leads to 5 year survival rate of 5 to 20 %. Various studies showed the rate of noncurative resections of 15-35 % [2][3][4][5], but with modified pathological examination (R1/R2) revealed the rate of R1 resection was higher ranging from 76-85 % [6][7][8][9]. Also autopsy studies in patients who died with pancreatic cancer showed 100 % local recurrence.…”
Section: Introductionmentioning
confidence: 99%